Rhizobia: a potential biocontrol agent for soilborne fungal pathogens - Das, Krishnashis; Prasanna, Radha; Saxena, Anil Kumar (Folia microbiologica, 2017)
Rhizobia are a group of organisms that are well known for their ability to colonize root surfaces and form symbiotic associations with legume plants. They not only play a major role in biological nitrogen fixation but also improve plant growth and reduce disease incidence in various crops. Rhizobia are known to control the growth of many soilborne plant pathogenic fungi belonging to different genera like Fusarium, Rhizoctonia, Sclerotium, and Macrophomina. Antagonistic activity of rhizobia is mainly attributed to production of antibiotics, hydrocyanic acid (HCN), mycolytic enzymes, and siderophore under iron limiting conditions. Rhizobia are also reported to induce systemic resistance and enhance expression of plant defense-related genes, which effectively immunize the plants against pathogens. Seed bacterization with appropriate rhizobial strain leads to elicitation and accumulation of phenolic compounds, isoflavonoid phytoalexins, and activation of enzymes like L-phenylalanine ammonia lyase (PAL), chalcone synthase (CHS), peroxidase (POX), polyphenol oxidase (PPO), and others involved in phenylpropanoid and isoflavonoid pathways. Development of Rhizobium inoculants with dual attributes of nitrogen fixation and antagonism against phytopathogens can contribute to increased plant growth and productivity. This compilation aims to bring together the available information on the biocontrol facet of rhizobia and identify research gaps and effective strategies for future research in this area.
Keywords: půdní mikrobiologie; Plant Diseases; Fungi; nemoci rostlin; antibióza; fixace dusíku; vývoj rostlin; Plant Roots; kořeny rostlin; Soil Microbiology; Plant Development; houby; Nitrogen Fixation; Antibiosis; Rhizobium